Elective coronary stenting of the target vessel affects the fractional flow reserve value of a stenosis in the non-target vessel: clinical implications for assessing multivessel disease with a pressure wire. (22nd September 2015) - Hoole, SP; Heck, PM; Epstein, AC; Clarke, SC; Dutka, DP
Abstract : Introduction: Functional lesion assessment by fractional flow reserve (FFR) has the potential to guide multivessel disease (MVD) percutaneous coronary intervention (PCI) and improve outcome. However, the effect of target vessel stenting on subsequent FFR measurements in the non-target vessel stenosis is unknown. We hypothesised that target vessel stenting would change the non-target vessel FFR due to microvascular resistance perturbation. Methods and Results: We recruited 30 patients (age 64.4 years, 19% female) with MVD (>50% stenosis in ⩾2 vessels >2.5 mm in diameter) awaiting elective PCI. A Radi pressure-wire was placed in the non-target vessel distal to the stenosis and distal pressure, aortic pressure and saline bolus thermodilution transit time (Tmn) were measured at baseline and during adenosine-induced maximal hyperaemia (140 μg/kg per minute via the femoral vein). Measurements were recorded in the non-target vessel before and after stenting the target vessel. FFR, coronary flow reserve (CFR) and index of microvascular resistance (IMR) were calculated for the non-target vessel and the values compared. FFR increased in the non-target vessel after stenting the target vessel (0.82 (0.02) vs 0.84 (0.02), p = 0.06). This was particularly apparent in patients with low IMR at baseline (n  =  20, 0.78 (0.02) vs 0.82 (0.02), p = 0.01), in whom a significant increase in IMR (10.4 (0.9) vs 15.6 (2.1), p = 0.03) and a reduction in CFR (2.9 (0.3) vs 2.2 (0.3), p = 0.02; fig) were observed. Conclusion: Elective target vessel stent implantation increases non-target vessel FFR values due to an increase in remote microvascular resistance that diminishes coronary flow. This has clinical implications in the guidance of MVD PCI using pressure wire.